Hubungan Religiusitas Dan Psychology Well Being Pada Mahasiswa Perantau Di UIN SU - Dona Dwi Novita; Siti Asyaroh; Windy Sakila Nazwa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to investigate the close relationship between the level of religiosity and psychological well-being in students of the Islamic Broadcasting Communication Department at the Faculty of Da'wah and Communication at UIN SU. By adopting a quantitative approach, this research involves active participants in the program and uses proven measurement instruments. By collecting data using a structured questionnaire, this research analyzes the level of religiosity and psychological well-being of students, and explores the relationship between the two. The results of statistical analysis show that there is a significant positive relationship between the level of religiosity and psychological well-being in students of the Islamic Broadcasting Communication Department. These findings support the concept that appreciation of religious values ​​and involvement in religious practices can make a positive contribution to students' psychological well-being. The practical implication of this research is the need to pay attention to religious aspects in the development of academic programs, as well as providing appropriate psychological support for students who seek a balance between academic demands and religious values.